Analysis of Targeted Post-operative Nursing Outcome in 1246 Patients with Percutaneous Transhepatic Biliary Drainage - Yang, Xiuchun; Qin, Yuelan; Mo, Wei; Xiang, Hua; Liu, Zhichao; Long, Jianhua; Xiang, Bin (Frontiers in Surgery, 2022)
Jaundice is a detection index in many disease conditions commonly characterized by yellowish staining of the skin and mucous membranes. This work studies the postoperative care outcome in 1246 patients (669 males and 577 females) with obstructive jaundice who underwent percutaneous transhepatic biliary drainage (PTBD). These patients were admitted to the interventional vascular surgery department of our hospital from February 2017 to February 2022. From the results, frequent wound re-dressing and maintenance of the drainage tube had significant positive influence on wound healing and patient recovery. The data also showed strict adherence by patients to the doctor’s recommendation advising them to visit the interventional specialist care clinic in time for wound dressing change and drainage tube maintenance. As a result, there was no significant difference in wound allergy, exudation, redness and loosening among patients. A cross-sectional analysis of the effect of age on recovery revealed variations in the healing pattern (wound loosening and the redness) between patients of different ages although the relationship is not very clear due to the limited sample size. Efficient drainage tube maintenance promoted recovery and prevented the occurrence of related complications such as PTBD tube blockage and biliary tract infection. The establishment of the interventional specialist care clinic used in this study additionally ensures patients’ safety, and the incidence of complications have been reduced drastically. These achievements are attributable to the implementation of regular dressing change, drainage tube maintenance and health education for patients with PTBD tube. These practices have also improved on the level of specialty in nursing practice, increased the professional value of nurses and better recognition by the society.